Oxygen vacancy-driven spin-transfer torque across MgO magnetic tunnel junctions - L. M. Kandpal; B. Taudul; E. Monteblanco; A. Kumar; K. Katcko; F. Schleicher; P. Gupta; S. Boukari; W. Weber; V. Da Costa; J. D. Costa; T. Bӧhnert; et al. (npj Spintronics)
Abstract Flowing an electrical current that is both of high areal density and large spin polarization across a magnetic tunnel junction (MTJ) can, through spin-transfer torque (STT), alter the relative magnetic orientation of the MTJ’s ferromagnetic electrodes. This effect has enabled key next-generation MTJ applications and commercialized products, from memories to artificial synapses and energy harvesters. As MTJs are now downscaled to 2 nm, basic experimental data challenge the accepted understanding of their operation. From transport spectroscopy, ferromagnetic resonance experiments and ab-initio calculations it is revealed that the high conductivity of STT-ready MTJs, and the STT effect therein, is mediated by oxygen vacancy complexes within the MgO barrier. Our work positions the oxygen vacancy at the core of MgO spintronics. This should disrupt the status-quo on STT-MRAM R&D, by generating defect-specific research and new ideas to confer additional functionality to these next-generation electronic devices, as a nanoelectronics platform to industrialize quantum physics.